The effect of religiosity and moderation of morality on fraud prevention in the management of village funds - Nur Hayati; Ikklimatus Amalia (The Indonesian Accounting Review, 2021)
This study aims to determine the effect of village apparatus competence, internal control systems and religiosity on fraud prevention in the village fund management with morality as a moderating variable. This study uses a survey method with a questionnaire. The population consists of all village officials in Sidoarjo Regency. The sample was taken using a proportionate stratified random sampling, and finally 76 villages were obtained with the category of developed villages, developing villages, underdeveloped villages, and very underdeveloped villages. The data analysis technique used in this study is PLS-SEM using Smart-PLS 3.0 software. The results of this study prove that village apparatus competence has an effect on fraud prevention in village fund management, internal control system has no effect on fraud prevention in village fund management, and religiosity has an effect on fraud prevention in village fund management.Morality is not able to moderate the influence of village apparatus competence, internal control system and religiosity on fraud prevention.